Activation of spleen cells by ArtinM may account for its immunomodulatory properties - da Silva, Thiago Aparecido (Springer Berlin Heidelberg, 2014)
ArtinM is a D-mannose-binding lectin extracted from Artocarpus heterophyllus that promotes interleukin-12 production by macrophages and dendritic cells. This property is considered responsible for T helper 1 immunity induced in vivo after ArtinM administration. In this study, we investigated the effect of native (jArtinM) and recombinant (rArtinM) forms of lectin on murine spleen cells and isolated T lymphocytes. We found that ArtinM binds to the surface of spleen cells. This interaction, which was blocked by D-mannose, induced cell activation, as manifested by increased mitochondrial activity, interleukin-2 production, and cell proliferation. We verified that a 30-times higher concentration of rArtinM was required to trigger optimal activation of spleen cells compared with that needed with jArtinM, although these proteins have identical sugar recognition properties and use the same signaling molecules to trigger cell activation. Because the distinction between native and recombinant is restricted to their tertiary structure (tetrameric and monomeric, respectively), we postulated that the multi-valence of jArtinM accounts for its superiority in promoting clustering of cell surface glycoreceptors and activation. The jArtinM and rArtinM activation effect exerted on spleen cells was reproduced on purified CD4(+) T cells. Our results suggest that ArtinM interaction with T cells leads to responses that may act in concert with the interleukin-12 produced by antigen-presenting cells to modulate immunity toward the T helper 1 axis. Further studies are necessary to dissect ArtinM/T-cell interactions to more fully understand the immunomodulation induced by carbohydrate recognition.